Commonwealth Caribbean property law - Kodilinye, Gilbert (Commonwealth Caribbean law series, 2022)
"This 5th edition of Commonwealth Caribbean Property Law sets out clearly and concisely the central principles of the law of real property in the region, guiding students through this core but often complex subject area. Fully revised and updated to include important new case law from the various Caribbean jurisdictions, the book provides comprehensive coverage of the key topics studied by undergraduates, including co-ownership, leaseholds, condominium, restrictive covenants, easements, mortgages and adverse possession. Emphasis is on those areas that are most commonly litigated in the region, and the book contains discussion of, or reference to, many unreported cases. This new edition features expanded coverage of freehold estates, a glossary of key terms, and a new question and answer section at the end of the book. Commonwealth Caribbean Property Law is essential reading for LLB students in Caribbean universities and students on CAPE Law courses and, with its analysis of the substantive laws across several jurisdictions, it will continue to be an invaluable reference tool for legal practitioners in the region"--